Numerical study on migration of overlying strata and propogation of cracks during multi-coal seams mining - Zou, Junpeng; Wang, Man; Bai, Lu; Yan, Chongwei (Frontiers in Earth Science, 2023)
The surface subsidence caused by the coal seam mining seriously affects the ecology of the mining area. Compared with the single-coal seam mining, the mechanism of the overburden fracture and crack propagation caused by multi-coal seams mining is more complex, which has not been fully understood. Taking the 22,108 and 42,108 working faces of Buertai Coal Mine as a research object, the discrete element method is used to simulate the migration and failure characteristics of overlying strata, and the propogation of cracks in the process of multi-coal seams mining is also been investigated. So many cracks develop in the soft strata overlying the coal seam, and they cross each other and form a complex fracture system. The hard layer produces staggered cracks with a large size, mainly high-angle longitudinal cracks. The surface subsidence curve of the single coal seam mining shows a wide and slow “bowl” type, and the surface subsidence curve of the double coal seams mining show a “funnel” type with only one inflection point. The overburden structure disturbance caused by the previous coal seam and rock cracking—settlement have great influence on the mining of the latter coal seam. The research results are basically consistent with the field data comparison, which could provide a reference for the related research and engineering practice of shallow-buried double coal seam mining.